1981
DOI: 10.3109/00498258109045298
|View full text |Cite
|
Sign up to set email alerts
|

Identification of urinary mercapturic acids formed from acrylate, methacrylate and crotonate in the rat

Abstract: 1. After administration to rats of methyl acrylate (I), methyl methacrylate (II) and methyl crotonate (III), urinary mercapturic acids were isolated and identified as the dicarboxylic acids N-acetyl-S-(2-carboxyethyl)cysteine (IV, R = H), N-acetyl-S-(2-carboxypropyl)cysteine (V, R = H) and N-acetyl-S-(1-methyl-2-carboxyethyl)cysteine (VI, R = H) and for a minor part as their monomethyl esters IV (R = CH3) and VI (R = CH3). 2. After a single dose of the acrylates (I), (II) and (III) (0.14 mmol/kg), the excretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…In other studies, mercapturic acids were found in the urine of rats given methyl acrylate by intraperitoneal injection. Pretreatment of the rats with TOTP resulted in increased levels of thioethers in the urine [31]. These results indicate that degradation via the unspecific carboxylesterase and SH conjugation are alternative pathways of methyl acrylate metabolism.…”
Section: Metabolismmentioning
confidence: 54%
See 1 more Smart Citation
“…In other studies, mercapturic acids were found in the urine of rats given methyl acrylate by intraperitoneal injection. Pretreatment of the rats with TOTP resulted in increased levels of thioethers in the urine [31]. These results indicate that degradation via the unspecific carboxylesterase and SH conjugation are alternative pathways of methyl acrylate metabolism.…”
Section: Metabolismmentioning
confidence: 54%
“…After occlusive application to the skin, methyl acrylate was absorbed only slowly and so weak radioactivity was detected in the urinary bladder and in other organs only after 16 and 28 hours (after local irritation and corrosion and local retention of radioactivity). During this time metabolism of the substance took place mostly in the skin where a large part of the radioactive material was also retained [20,21].…”
Section: Metabolismmentioning
confidence: 99%
“…The most prominent effects of occupational chemical exposures detected so far have been dermatologic problems and spontaneous abortions among operating room personnel. In addition to the chemical risks dealt with in this review, there are many other potential chemical hazards related to, eg, the use of plastic biomaterials (19,39,62,74). While the well-established infection diseases must not be forgotten, more emphasis should be placed in the future on the possible chemical hazards in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…After administration of the esterase inhibitor, TOTP 7 (0.34 mmol/kg in arachis oil 18 hours before injection with methyl crotonate), there was a significant increase in urinary thioether excretion as compared to the controls (increasing from 2 to 16% of the dose), indicating that hydrolysis by carboxylesterase influences conjugation with glutathione in that the ester (methyl crotonate) reacts more readily in a Michael-type reaction with glutathione than the unesterified crotonic acid (Delbressine et al, 1981a).…”
Section: Studies On Individual Candidate Substancesmentioning
confidence: 98%
“…This reaction may lead to glutathione depletion after i.p administration. When ester hydrolysis is inhibited by pre-treatment with TOTP 7 , the urinary excretion of these conjugates is strongly increased, indicating that only the ester but not the free unsaturated acid is subject to this conjugation reaction (Delbressine et al, 1981a). This conjugation has been observed after intraperitoneal injection of the esters, and it is questionable whether it is very relevant after oral exposure, due to presystemic ester hydrolysis.…”
Section: Ester Conjugation With Glutathionementioning
confidence: 99%